Hearing the Wind Again - Linda Antas (Journal of the Association for Technology in Music Instruction, 2025)
I love listening to the wind blow through the forests and mountains—hearing its pitch and timbre change, its approaching and passing, and its power. This piece was inspired by the sound of the wind, and my mother’s tears at hearing the wind. Before getting hearing aids, she hadn’t heard it for years.
Keywords: composition